Technology Factors Affects the Adaptation of the Current Sport Broadcasters - Promchim, Supakit; Piromnum, Suticha (Journal of Management Science Nakhonratchasima University, 2022)
This research was aimed to study the technology factors affecting the performance of the sports broadcasters at present. The research was a qualitative research. Data were collected by using an in-depth interview. There were 6 interviewees; 3 television broadcasters and 3 online sports programmers. The results of the study found that currently the technology plays a huge role in the work. Technology makes work easier and more comfortable. However, integrating the old work style with the new one could run the work more efficiently. The world spins, the technology also spins, and there will be the differences between the past and the present. The difference in terms of presenting the news, that can be discussed by using technology, can lessen the work-flow. Currently, the technology can reduce the workload and the wages. This is suitable for the current situation. The disadvantage is the staffs reduction which affects people working in the career and those in the news search process. As the news quickly and broadly spread, the broadcasters and the audiences must have the media literacy. At present, the sports broadcasters have to adapt to the modern technology instead of being attached to the traditional one. They must be not afraid of the changes and be ready to learn new happenings. The sport broadcasters must learn and adapt themselves to the modern technology as a tool to facilitate the work. Moreover, they must improve themselves along with the technology.